Rethinking teacher education in an AI world: perceptions, readiness and institutional support for generative AI integration - Ó Ceallaigh, T. J.; O’ Brien, Emma; Tømte, Cathrine; Kulaksız, Taibe; Connolly, Cornelia (European journal of teacher education, 2025)
The increasing prevalence of Generative AI (GenAI) in education offers significant opportunities for advancements in instructional design and educational innovation. GenAI tools, like ChatGPT, are poised to transform teacher education by reshaping instructional techniques, learning strategies, and assessment methods. However, there is limited research on educational institutions’ responses to GenAI and teacher educators’ readiness to adopt these tools. This study, part of a larger Delphi project, examines the adaptations needed in teacher education programmes to prepare teacher educators for an AI-driven future. Utilising an extensive online questionnaire, data from 138 teacher educators across Europe reveal a critical need for comprehensive support from institutions, highlighting the importance of developing essential AI competencies, adopting innovative pedagogical approaches, and creating policies that responsibly integrate GenAI. These findings provide a foundation for crafting forward-thinking strategies to harness GenAI’s potential in enhancing 21st-century teaching and learning outcomes.
Gesehen am 02.02.2026